A Co–N4 moiety embedded into graphene as an efficient single-atom-catalyst for NO electrochemical reduction: a computational study. Issue 17 (11th April 2018) - Wang, Zhongxu; Zhao, Jingxiang; Wang, Jingyang; Cabrera, Carlos R.; Chen, Zhongfang
Abstract : Co–N4 -embedded graphene exhibits superior catalytic performance for NO electrochemical reduction with a lower onset potential than that of Pt-based catalyst. Abstract : Electrochemical reduction of nitric oxide (NOER) is a promising technology for the removal of harmful N-containing species in groundwater under mild conditions. In this work, by means of density functional theory computations, we systematically investigated the potential of utilizing experimentally feasible transition metal–N4 /graphenes as NOER catalysts. Our results revealed that NO molecules can be moderately activated on a Co–N4 moiety embedded into graphene, and the subsequent NOER steps can proceed to form either NH3 at low coverages or N2 O at higher coverages. Especially, the computed onset potential of NOER on Co–N4 /graphene ( ca. −0.12 V) is comparable to (or even better than) those on well-established Pt-based catalysts. Thus, Co–N4 /graphene is a promising single-atom-catalyst with high efficiency for NO electrochemical reduction, which opens a new avenue for NO reduction for environmental remediation.